Narrative criminology : understanding stories of crime - Presser, Lois; Sandberg, Sveinung (Alternative criminology series., 2015)
Stories are much more than a means of communication-stories help us shape our identities, make sense of the world, and mobilize others to action. In Narrative Criminology, prominent scholars from across the academy and around the world examine stories that animate offending. From an examination of how criminals understand certain types of crime to be less moral than others, to how violent offenders and drug users each come to understand or resist their identity as 'criminals', to how cultural narratives motivate genocidal action, the case studies in this book cover a wide array of crimes and j.